Formulation and evaluation of wound healing activity of sophorolipid-sericin gel in wistar rats - More, V. Snehal; Koratkar, Santosh S.; Kadam, Navnath; Agawane, Sachin; Prabhune, Asmita (Pharmacognosy Magazine, 2019)
Sericin is a useful by-product of silk processing and is resistant to oxidation and ultraviolet and can absorb and release moisture easily. Sericin has biological activities such as antibacterial, antioxidant, and tyrosinase inhibition. Sophorolipids are microbial extracellular glycolipids produced by resting cells of Candida bombicola. Sophorolipids show excellent skin compatibility and also have antibacterial property. In this study, we have developed a novel formulation consisting of sericin and sophorolipid with calcium alginate as a binding agent. Since both the ingredients are biocompatible and biodegradable, the formulation was tested for wound healing in Wistar rats. A commercial ointment povidone was used as control. The animal group, treated with sericin and sophorolipid cream, showed fast contraction, rapid closure, and healing when compared with control and commercial ointment. These observations were validated with histopathological studies where more fibroblast proliferation, angiogenesis, and keratinization were observed. This is a green, cost-effective formulation for fast wound healing.
Keywords: Biocompatibility; formulation; sericin; Sophorolipid; wound Healing